RESEÑAS - Butinyà, Júlia; Sánchez Rei, Xosé Manuel (Revista de lenguas y literaturas catalana, gallega y vasca, 2022)
RESEÑAS DE: Biografies invisibles. Invisible Biographies, Marginats i marginals. Marginates and Marginals, Vicent Josep Escartí ed., John Benjamins Publications Company, dins la col·lecció: «IVITRA research on Linguistics and Literature. Studies, Editions and Translations», vol. 28. Amsterdam/Philadelphia, 2021. ISBN 9789027209207 Antoni Ferrando + Anna Maria Babbi (eds.). La «cavalleria umanistica» italiana / The italian «Humanistic Chivalry». Enyego (Inico) d’Avalos e ‘Curial e Güelfa’ / Enyego (Inico) d’Avalos and ‘Curial e Güelfa. «IVITRA. Research in Linguistics and Literature» 29. Amsterdam / Philadelphia: John Benjamins Publishing Company 2021, 208 pp. ISBN: 978-90-272-0928-3 Freixeiro Mato, Xosé Ramón, Idioma e sociedade. Sobre normalización e planificación da lingua galega, Santiago de Compostela, Laiovento, 2020, 294 pp. [ISBN 978-84-8487-184-3].